Numerical investigation of cooling ability in heat-generating porous debris bed after severe accident in PWR - Xu, Junying; Dong, Xiaomeng; Zhang, Huiyong; Yun, Xiangyu; Zhang, Lei; Ye, Yuzhao; Liu, Xiang; Mo, Jinhong; Yang, Ming (Frontiers in Energy Research, 2023)
A porous debris bed formed after a severe accident is a structure composed of different sized particles. Due to the fission reaction in the debris bed, decay heat is continuously released. Therefore, the cooling ability should be investigated to determine the safety of the debris bed. In this paper, two-phase conservation equations with closure correlations are proposed for the boiling phenomenon inside the pool. For the flow resistance, the drag force between the gas and liquid in the continuous fluid is considered as well as the flow resistance of the solid to fluid in the porous medium area. The heat transfer model takes into account the heat transfer between solid phase and fluid phases as well as the heat and mass transfer between gas and liquid. All calculations are conducted based on the CFD method, and the related models are written into the CFD calculation program in the form of a User Defined Function (UDF). After the necessary validation of the proposed correlations, the analysis and discussion are based on the effect of the heating type, the non-uniform distribution of structural parameters, and the shape of the geometry. The results show the key effect of natural convection between the different boundary settings of the heating type. The time series of strong natural convection formation and the decay power of heat are the factors that are determined for the position of the boiling crisis. In addition, the limited power density is determined by the top half of the debris bed. The increase in structural parameters and operating pressure leads to a better cooling ability. For the shape of the debris bed, a regular cylinder is a better structure for heat removal, while the conical shape significantly reduces the limited power density, which is dangerous for the long-term cooling of the debris bed. The cooling ability would be improved if a downcomer existed in the porous debris bed. These three research parts are conducive to deepening the understanding of the process of a serious accident.